Physical activity and substance use among Canadian adolescents: Examining the moderating role of school connectedness - Fagan, Matthew James; Duncan, Markus J.; Bedi, Robinder P.; Puterman, Eli; Leatherdale, Scott T.; Faulkner, Guy (Frontiers in Public Health, 2022)
Physical activity may play a role in promoting or preventing substance use among youth. The purpose of this study was to examine the association between different types of physical activity [i.e., non-competitive school sport, competitive school sport, outside of school sport and minutes of moderate to vigorous physical activity (MVPA) per day] and substance use (i.e., current smoking, e-cigarette, cannabis, binge drinking) among Canadian youth. Interaction effects between physical activity and school connectedness were also examined. Using data from the COMPASS study (2018–19; n = 73,672), four multi-level logistic regression models were developed to investigate whether physical activity lessened or worsened the odds of (1) smoking; (2) e-cigarette use; (3) cannabis use; and (4) binge drinking. Models were stratified by gender to reflect the inherent differences between genders. Models were adjusted for demographic factors and other covariates. Sport participation was consistently associated with substance use, whereas less evidence was found for meeting MVPA guidelines. Non-competitive school sport lessened the odds of cannabis use for males and females. However, non-competitive school sport only lessened the odds of e-cigarette use for females but increased the odds of binge drinking for males. Participation in competitive school sport lessened the odds of cigarette smoking but increased the odds of e-cigarette use and binge drinking for males and females. Outside of school sport lessened the odds of cigarette smoking and cannabis use but increased the odds of e-cigarette use and binge drinking for males and females. A significant moderation effect was found for males participating in sport outside of school and meeting MVPA guidelines who were at a lower risk of e-cigarette use in the presence of high levels of school connectedness. Our study provides evidence for further consideration and provision of extracurricular activities, specifically non-competitive sport, in protecting against substance use. Caution is required in claiming that sport participation or physical activity, in general, is negatively associated with substance use among youth.